Time and International Adjudication : The Temporal Factor in Proceedings before International Courts and Tribunals - Dimetto, Marco,; Gattini, Andrea, (International Law E-Books Online, Collection 2025., 2025)
Time and International Adjudication fills a gap in legal literature in the field of international dispute settlement, by providing a wide selection of stimulating contributions by leading international scholars and lawyers, aimed at discussing the role of time in proceedings before international courts and tribunals. The relevance of the temporal factor in international adjudication is assessed by considering each of the different phases of international judicial proceedings. The analysis covers inter-State proceedings before both permanent courts and tribunals (such as the ICJ, ITLOS and the DSB of the WTO) and arbitral tribunals, as well as international proceedings between individuals and States before regional human rights courts and investment tribunals.